Resorption of Lateral Incisors during Canine Eruption: Two Clinical Cases with Focus on Root Lengths and Heredity - Mostafa Zargham; Inger Kjær (Wolters Kluwer Medknow Publications, 2016)
Introduction: It is well-known that pressure from orthodontic appliance can provoke root resorption in dentitions with short roots. The purpose of this case report is to demonstrate two clinical cases with focus on root length in dentitions exposed due to pressure from erupting teeth. This is a pilot study aimed to improve diagnostics for avoiding the resorption of lateral maxillary incisors by pressure from erupting canines. Case Report: The first reported case is of a girl who was 11 years and 7 months old when radiographs showed severe resorption of the lateral incisors, along with malformed central incisors and short roots. The intraoral photos demonstrated light crowding in the maxilla. The orthopantomogram of the girl's mother demonstrated several short roots. The second reported case is of a girl who was 9 years and 5 months old when radiographs demonstrated nearly complete resorption on her lateral incisor roots, extremely short roots in the central incisors, and short roots. The intraoral photos demonstrated light crowding in the maxilla. The orthopantomogram of the girl's mother demonstrated extremely short roots in general. Conclusion: This pilot study indicates that short root length in general and abnormal incisor morphology are phenotypic traits that were characteristic for both girls who presented with severe lateral incisor resorption due to erupting canines. Furthermore, short roots were also demonstrated in the mothers. Accordingly, short root length in general could be a phenotypic trait, which should be diagnosed early for preventing severe resorption of lateral incisors during canine eruption.